Influence of composite elastic modulus and lateral load pattern on deflection of anti-slide pile head. Issue 3 (2nd April 2016) - Li, Changdong; Liu, Qingtao; Hu, Xinli; Wang, Liangqing; M. A. M, Ez Eldin
Abstract: This paper develops a new method to directly determine the composite elastic modulus of the reinforced con- crete cantilever pile rather than adopt theoretical or empirical approaches. On the basis of the theory of material mecha- nism, the load-deflection equation was deduced to create the relationship between the elastic modulus and the ratio of load-deflection. The numerical modelling tests based on ANSYS separation modelling technology were carried out to determine the composite elastic modulus under different reinforcement ratio, concrete strength grade and distribution pat- tern of driving force. The results can be used to create the quantitative relationship between the composite elastic modulus and reinforcement ratio as well as concrete strength grade. Comparison amongst various lateral load pattern were made to show that the deflection of pile head is obviously affected by the lateral load pattern, and the corresponding equations of the deflection of the pile head under different lateral load pattern were proposed, which can reflect the ranking of the great influence on the deflection of the pile head, rectangular, trapezoidal and triangular lateral load pattern in order.